Industrial Revolution 4.0, Tech Giants, and Digitized Societies - Lim, Tai Wei.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Industry 4.0 explores the emergence of disruptive digital technologies such as robotics, blockchain, nanotechnology and 3D printing and their impact on human lives and jobs in globalized 21st century societies. Incorporating a cutting edge area studies perspective, it considers the challenges and long term implications of the rise of 'Tech Giants' such as Alibaba, Google and Baidu through the lens of past industrial revolutions, looking back at the transformative technologies and industrial developments - the steam engine, electrification, telegraph, mass production, and the rise of digital technology - upon which the modern world was built. It investigates the mirror profiles of the world's largest tech companies in the US and China (Baidu and Google, Alibaba and Amazon, Wechat and Facebook) and provides a unique comparison of Tech Giants with 19th century colonial empires and monopolistic trading companies in terms of political-economic dominance. A key tool for instructors and students focused on courses on Technological History, Digital Technology and Cultures, New Media, Digital Ethics and China studies, this book provides practical guidance on how readers can equip themselves to face key workplace and societal challenges in a virtually interconnected world shaped by Tech Giant monopoly.
Part A Section on Industrial Revolution 4.0, Tech giants, and Digitized societies -- Tech Giants, Digitized Workplaces and Societies: Comparative area studies analyses of North American and East Asian responses to Industrial Revolution 4.0 -- Digital Disruptions and the Workplace -- The Internet of Things (IoT) -- The Rise of Smart Cities -- Conclusion -- Part B Section on Specific Case Studies -- Case Study 1 - Japan's Foreign Talent Policy and the Future of Robot Replacements -- Case Study 2 - Service Learning -- Case Study 3 - The Rise of Smart Cities in China - Domestic development and comparative perspectives -- Case Study 4 - 'Active Aging' and 'Healthy Aging': a comparative survey of coping mechanisms for greying populations in Japan and Hong Kong -- Case Study 5 - Cashless Convenience in China - A survey of its development and a case study of the political economics behind the Mechanism -- Case Study 6 - A Traditional SME (Small and Medium Enterprise) in Singapore Turns to Digital Technologies for Boosting Retail Business -- Part C Section on Quizzes -- Quiz 1: Tech Giants, Digitized Workplaces and Societies Quiz -- Quiz 1: Digital Disruptions and the Workplace Quiz -- Quiz 1: IoT -- Quiz 1: Rise of Smart Cities -- Quiz 1: Section A: Drawn from Chapter A5 Conclusion -- Quiz 1: Section A: Drawn from Chapter B4 Case Study 4.
Keywords: Industrial sociology; Social history; Educational technology; Political sociology; Career education; Sociology of Work; Social History; Digital Education and Educational Technology; Political Sociology; Career Skills